Analysis of the Application of Sharia Principles in the Development of Sharia Capital Market (Case Study of the Indonesia Stock Exchange, North Sumatra Representative Office) - Muhammad Ikhsan Harahap; M. Ali (Penerbit Jurnal Indonesia, 2022)
The problem in this study is whether the application of sharia principles is in accordance with the principles of the sharia capital market according to the DSN-MUI Fatwa NO: 40/DSN-MUI/X/2003 and POJK 15/POJK.04/2015. This study aims to determine the suitability of the application of sharia principles in the development of the Islamic capital market at the Indonesia Stock Exchange, North Sumatra Representative Office. The results of this study are expected to be able to provide input in the world of capital markets, especially in the Islamic Capital Market. This research was conducted at the Indonesia Stock Exchange Representative Office of North Sumatra. The data in this study are primary data and secondary data. The research method used is qualitative with a qualitative descriptive approach with the aim of providing a detailed description of the background, characteristics, and characteristics of the subject under study. The results of this study indicate that the application of sharia principles in the development of the Islamic capital market at the Indonesia Stock Exchange North Sumatra Representative Office has been in accordance with the principles of the Sharia Capital Market according to the Fatwa of DSN-MUI NO: 40/DSN-MUI/X/2003 and POJK 15/ POJK.04/2015.